Time series of chicken stool metagenomics and egg metabolomics in changing production systems: preliminary insights from a proof-of-concept - Michael E. G. Rosch; Jacqueline Rehner; Georges P. Schmartz; Sascha K. Manier; Uta Becker; Rolf Müller; Markus R. Meyer; Andreas Keller; Sören L. Becker; Verena Keller (BMC, 2024)
Abstract Background Different production systems of livestock animals influence various factors, including the gut microbiota. Methods We investigated whether changing the conditions from barns to free-range chicken farming impacts the microbiome over the course of three weeks. We compared the stool microbiota of chicken from industrial barns after introducing them either in community or separately to a free-range environment. Results Over the six time points, 12 taxa-mostly lactobacilli-changed significantly. As expected, the former barn chicken cohort carries more resistances to common antibiotics. These, however, remained positive over the observed period. At the end of the study, we collected eggs and compared metabolomic profiles of the egg white and yolk to profiles of eggs from commercial suppliers. Here, we observed significant differences between commercial and fresh collected eggs as well as differences between the former barn chicken and free-range chicken. Conclusion Our data indicate that the gut microbiota can undergo alterations over time in response to changes in production systems. These changes subsequently exert an influence on the metabolites found in the eggs. The preliminary results of our proof-of-concept study motivate larger scale observations with more individual chicken and longer observation periods.